Effects of the PKC inhibitor PD 406976 on cell cycle progression, proliferation, PKC isozymes and apoptosis in glioma and SVG‐transformed glial cells - Russell, C. (Cell Prolif, 2005)
Abstract.  It is well established that protein kinase C (PKC) isozymes are involved in the proliferation of glioma cells. However, reports differ on which PKC isozymes are responsible for glioma proliferation. As a means to further elucidate this, the objectives of our research were to determine how inhibition of PKC‐α, PKC‐β and PKCµ with PD 406976 regulates the cell cycle, cell proliferation and PKC during glioma growth and development. To establish the cell cycle effects of PD 406976 on brain cells (SVG, U‐138MG and U‐373MG glioma cells), specimens were treated with either dimethylsulfoxide (DMSO; control) or PD 406976 (2 µm). Results from flow cytometry demonstrated that PD 406976 delayed the entry DNA synthesis phase in SVG cells and delayed the number of cells entering and exiting the DNA synthesis phase in both U‐138MG and U‐373MG cells, indicating that PD 406976 may inhibit G(1)/S and S phase progression. Assessment of cell viability demonstrated a cytostatic effect of PD 406976 on SVG, U‐138MG and U‐373MG glioma cell proliferation. The PD 406976‐induced decreased proliferation was sustained at 48–96 h. A PKC activity assay was quantified and demonstrated that exposure of SVG and U‐373MG glioma cells to PD 406976 suppressed PKC activity. Western blotting demonstrated reduced PKC‐β1, PKC‐γ and PKC‐τ protein content in cells treated with PD 406976. We determined that the growth inhibitory effect of PD 406976 was not as a result of apoptosis.